Production of DTM by using the existing contour data lines - Subedi, Nab Raj; Chhatkuli, Raja Ram (Journal on Geoinformatics, Nepal, 2007)
The topographic database in Nepal has been prepared in the national level by making use of the analogue topographic base data. Topographic dynamics in terms of other physical features changes rapidly but changes in the terrain elevation occurs negligibly. As there has been growing demand for digital height model (DHM) of the terrain in spite of the presence of the existing two and half dimensional data such as contours, work was done as to the input, methodology, and quality assessment of the DTM being generated on the national level. Some initiations taken in this respect has been highlighted in this paper.